2022
DOI: 10.1002/jdd.13021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about oral cancer among dental students and Primary Health Care dentists: A Brazilian study

Abstract: Purpose/objectives: The present study aims to evaluate the knowledge of dental students and dentists who work in Primary Health Care (PHC). These are professionals who work in the public basic health units regarding oral cancer prevention, diagnosis, and treatment. Methods:A cross-sectional and observational Brazilian study was conducted. A survey with 27 questions was carried out regarding the (i) demographic, academic, and professional data of the participants, (ii) attitudes, practices, and self-perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This improvement can be seen in each stage of their progress in the oral medicine and pathology courses. Although our results are consistent with previous reports (de Lima Medeiros et al, 2022; Kujan et al, 2013; Kujan et al, 2014), they may highlight the necessity of familiarizing students more with normal mucosal variations and OPMDs by implementing more clinical load in the oral medicine curriculum.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This improvement can be seen in each stage of their progress in the oral medicine and pathology courses. Although our results are consistent with previous reports (de Lima Medeiros et al, 2022; Kujan et al, 2013; Kujan et al, 2014), they may highlight the necessity of familiarizing students more with normal mucosal variations and OPMDs by implementing more clinical load in the oral medicine curriculum.…”
Section: Discussionsupporting
confidence: 92%
“…The overall accuracy of differentially diagnosing oral mucosal lesions among the participants was around 66%. This finding is comparable with previous studies that assessed didactic knowledge among dental care professionals in Brazil (de Lima Medeiros et al, 2022), Eastern Europe (Golburean et al, 2021) and the United Kingdom (Greenwood & Lowry, 2001), but is higher than that reported in studies from the United Arab Emirates (Gaballah et al, 2021) and Indonesia (Wimardhani et al, 2021). More importantly, this study showed that years of experience did not influence the ability to correctly diagnose oral mucosal lesions among the practising dental health professionals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation